2014
DOI: 10.1111/btp.12187
|View full text |Cite
|
Sign up to set email alerts
|

Testing Chronosequences through Dynamic Approaches: Time and Site Effects on Tropical Dry Forest Succession

Abstract: Chronosequences, commonly used to assess succession, have been questioned because of their failure to project successional trajectories. Here, we develop a simple analytical approach combining both chronosequence and dynamic data to test the power of age of abandonment and site factors to explain and predict succession. The approach proceeds by first fitting statistical models relating age to attribute values (the chronosequence model) and their observed changes (the dynamic model) to test explanatory power. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 59 publications
5
61
0
10
Order By: Relevance
“…Our results showed that successional pathways were highly idiosyncratic among nearby plots of the same age since abandonment with similar disturbance history, and therefore we strongly advise caution in making inferences about rates of vegetation change based on single-time censuses (27).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Our results showed that successional pathways were highly idiosyncratic among nearby plots of the same age since abandonment with similar disturbance history, and therefore we strongly advise caution in making inferences about rates of vegetation change based on single-time censuses (27).…”
Section: Discussionmentioning
confidence: 79%
“…Topographic variation in soil quality and drainage, distance to other forest patches, continuous changes in the surrounding landscape, initial species and functional composition, fire frequency, and neighborhood effects all influence rates of vegetation change in successional pathways (27). Moreover, a myriad of local factors including priority effects, invasive species, weed control, last crop planted, nutrient treatments, pathogen and herbivore loads, and persistent edge effects can alter successional processes and push community trajectories in unpredictable directions (18).…”
Section: Discussionmentioning
confidence: 99%
“…It is also likely that differences in initial establishment densities and subsequent sequences (or lack thereof) of Alnus, Picea, and other species, rather than time, drive some variation in N and C cycling noted in chronosequence studies (a concern noted by Bormann and Sidle [1990]). It could be this historical spatial heterogeneity, rather than environmental, topographic, or climatic variability, that is driving the substantial unexplained variation seen in modern chronosequence work in Glacier Bay and elsewhere (e.g., Mora et al 2015, Norden 2015, Malone et al 2018). More detailed investigations of C-cycling and biodiversity at the microbial and fungal are needed, especially those linking the above and belowground communities in relation to early successional history.…”
Section: Overall Impressionsmentioning
confidence: 99%
“…These researchers often took a dynamic view of the interactions between temporally distinct processes, from landform evolution to its influence on vegetation succession, and then, in turn, succession's influence on landform development and change, "a variable approaching a variable" in the words of Cowles (1901). Many ideas have become popular only to lose prominence, and occasionally be resurrected again (Egerton 2015), but the goal of predicting plant communities through time has remained a central pursuit in ecology (e.g., Mora et al 2015, Norden 2015. Many ideas have become popular only to lose prominence, and occasionally be resurrected again (Egerton 2015), but the goal of predicting plant communities through time has remained a central pursuit in ecology (e.g., Mora et al 2015, Norden 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, chronosequence data only permits inferences of successional change and do not facilitate the direct analysis of underlying processes that mediate the change, such as growth, mortality and recruitment (Chazdon et al 2007). The combination of chronosequencing and dynamics analyses can provide an effective tool to explain the changes in biomass (Mora et al 2015). In the present study, we examined the recovery and dynamics of aboveground biomass (AGB) after selective logging under SFM in a typical terra firme forest managed by a private company in the central Amazon.…”
Section: Introductionmentioning
confidence: 99%